Modelling and forecasting short-term electricity load: a two step methodology - Lacir J. Soares; Marcelo C. Medeiros (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2005)
The goal of this paper is to develop a forecasting model of the hourly electricity load demand in the area covered by an utility company located in the southeast of Brazil. A di®erent model is constructed for each hour of day, thus there are 24 di®erent models. Each model is based on a decomposition of the daily series of each hour in two components. The rst component is purely deterministic and is related to trends, seasonality, and special days e®ect. The second one is stochastic and follows a linear autoregressive model. The multi-step forecasting performance of the proposed methodology is compared with a benchmark model and the results indicate that our proposal is a useful tool for electricity load forecasting.
Keywords: 330; Elektrizitätswirtschaft; Energiekonsum; Brasilien (Südost)